Screening for nutrition risk and dysphagia among older adults newly admitted to age related residential care facilities in the Waitemata DHB region : a thesis presented in partial fulfillment of the requirements for the degree of Master of Science in Nutrition and Dietetics at Massey University, Auckland, New Zealand - Watkin, Rebecca Stephanie (Massey University, 2014)
Background: New Zealand has an ageing population, reflected by an older average population age and reduced mortality. Good nutrition is essential for successful ageing. Many factors are known to influence nutrition risk, and a high prevalence has been observed overseas in people living in age related residential care (ARRC) facilities. In New Zealand, there is limited data on both the prevalence of nutrition risk in ARRC facilities and the health factors that contribute to risk. The changing demographics of the population means that a greater understanding in this area will be important to develop strategies which support the maintenance of good nutrition status for longer, thus potentially reducing health burden. This study aims to determine nutrition risk and the risk of dysphagia (swallowing difficulties) in older adults recently admitted to an ARRC facility in the Waitemata District Health Board (DHB) region. Methods: Fifty-six individuals aged ≥65 years (or ≥55 years for Māori and Pacific) who were admitted for the first time to an ARRC facility within the Waitemata DHB region were invited to participate in the study. Potential contributors to nutrition risk were explored using a questionnaire that asked about nutritional and non-nutritional risk factors. The Mini Nutritional Assessment®-SF (MNA®-SF) was used to determine level of nutrition risk. Risk of dysphagia was identified using the Eating Assessment Tool (EAT-10). The Montreal Cognitive Assessment (MoCA) was carried out at the end of the interview and was used as a measure of cognitive function. Results: A total of 53 participants with a mean age of 88 years were included. Overall, 91% of the participants were either malnourished (47%) or at risk of malnutrition (43%). Normal nutritional status was only prevalent in 9% of participants. Fifty-seven percent of participants were widowed, of which, 52% were malnourished. When malnourished participants were compared to those with normal nutritional status, malnourished participants were more likely to be underweight, in hospital level care, have a recent severe decrease in food intake, recent weight loss of greater than 3kg, have poorer mobility, experienced psychological stress or acute disease and have severe dementia or depression. Malnourished participants were more likely to report weight loss of greater than 3 kg than those at risk of malnutrition (56% vs. 13% respectively, p = 0.03; Fisher’s exact test). Those who were malnourished had poorer mobility (χ2 = 8.592 p = 0.003) and were more likely to be at risk of dysphagia (χ2 = 6.273 p = 0.01) compared to those at risk of malnutrition. Participants in hospital level of care were also more likely to be at risk of dysphagia compared to those in rest home level of care (χ2 = 4.627 p = 0.03). ii Conclusions: These findings suggest there may be a high prevalence of nutrition risk among older adults newly admitted to ARRC facilities within New Zealand and that existing poor nutrition may have contributed to the need to move into ARRC. The predisposing factors that affect nutrition status warrant further investigation so initiatives can be undertaken to avoid a change in living situation. The results highlight the need for nutrition screening and early intervention by a dietitian.
Keywords: Older people; Older adults; Elderly; Nutrition; Malnutrition; Dysphagia; Residential care; Screening; Evaluation; Waitemata; New Zealand